KONSEP TAFSIR DAN TAKWIL DALAM PRESPEKTIF AS-SYATIBI - Jonwari Jonwari; Faiz Zainuddin (LP2M Universitas Ibrahimy, 2020)
As a religion that respects differences, interpretive differentiation thrives in Islam in accordance with the nature of its teachings which are accepting many interpretations. Therefore, differences and disagreements cannot be avoided in appreciating the moral messages contained in the dictums of religious teaching itself. Of course this fact is a very unique phenomenon in the Islamic scientific tradition which should be approved. Because this phenomenon can actually bless mankind on the earth, and at the same time can emphasize that Islam is a dimensional religion and always provides many alternatives in every spectrum of teachings. Therefore, interpretation must be seen as a dialectical process between the interpreter, the Al-Qur'an, and the changing reality. Therefore, the interpretation must become an intellectual tradition that must be preserved so that the guidance of Al-Qur'an is always in tune with the trends of the times that are constantly rolling. However, in its development, the intensity of the thought has deepened, a new phenomenon has emerged which gives birth to an adage that it turns out that Al-Qur'an is not a pure revelation of God. However, it is more of a dialectical product between the words of God and the socio-cultural reality which is the entry point of a text being revealed. So that an impression appears that implies Al-Qur'an as a cultural product. It becomes certain that in the process of extracting the meaning of Al-Qur'an, a methodical concept is needed that places its significance in linguistic studies, which of course does not ignore the objective-humanist factors.